Pengaruh Arus Kas Operasi dan Ukuran Perusahaan Terhadap Kinerja Keuangan - Megananda Megananda; Sri Wahyuni Jamal; Muhammad Iqbal Pribadi (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Transportation and logistics sector companies play an important role in supporting the distribution of goods and services in Indonesia. This sector includes land, sea, air transportation services, as well as supply chain management. This study aims to analyze the effect of operating cash flow and company size on financial performance in companies in this sector listed on the Indonesia Stock Exchange (IDX). Financial performance is measured by the return on assets (ROA) ratio. Data was obtained through the documentation method from the official IDX website and related company websites. The sample was determined by purposive sampling method. The analysis technique used is multiple linear regression. The results showed that operating cash flow has a significant effect on financial performance. Company size also has a significant effect on financial performance. These findings indicate that internal factors such as operating cash flow and company scale affect the financial performance of transportation and logistics sector companies.